A model of vesicle tubulation and pearling induced by adsorbing particles. Issue 20 (24th April 2015) - Su, Yu-Cheng; Chen, Jeff Z. Y.
Abstract : A transition path sequence is found, similar to the observation in a recent experiment, for the tubulation and pearling transition of a vesicle immersed in a nanoparticle solution. Abstract : We study the basic theoretical model of a deformable vesicle immersed in a solution of particles that can adsorb onto one of the two surfaces of a membrane. The model consists of an adsorption energy gain for the adsorbing particles and the Canham–Helfrich membrane bending energy, in which the spontaneous curvature is coupled with the adsorption area. We demonstrate that bud, pearling, and tube conformations can be stabilized after minimizing the free energy and that the pearling–tubulation transition has the characteristics of an abrupt structural transition.